Does twinkle artifact truly represent a kidney stone on renal ultrasound?. Issue 4 (August 2021) - Puttmann, Kathleen; Dajusta, Daniel; Rehfuss, Alexandra W.
Summary: Introduction: Nephrolithiasis is detected on ultrasound by the presence of an echogenic focus, posterior acoustic shadowing and/or twinkle artifact (TA). TA has been shown to be highly predictive of nephrolithiasis in adults with renal colic and ureteral stones. We sought to evaluate if TA is reliable for diagnosing nephrolithiasis in the pediatric population. Methods: We reviewed renal ultrasound reports indicating presence or absence of TA associated with a single echogenic focus in the kidney or ureter. Exclusion criteria were age >18, multiple echogenic foci or medullary calcinosis, no follow-up, or TA located outside the kidney or ureter. Stone was confirmed either by CT within 3 months of color Doppler ultrasound, visualization on ureteroscopy, or patient report of passing the stone. Results: Five hundred and ninety-nine ultrasound reports were reviewed and 293 met inclusion criteria. Sixty-nine had diffuse twinkle without echogenic focus and 224 showed TA with single echogenic focus. 135 patients had confirmatory information available (Summary Table). Nephrolithiasis was diagnosed using TA and confirmed on confirmatory studies for 49 ultrasounds. The majority of confirmed stones were in the kidney (n = 40; 82%) and mean size of confirmed stones on ultrasound was 5 mm (range 1.5–10). Sensitivity, specificity, positive predictive value and negative predictive value of TA for detecting nephrolithiasis were 83%, 78%, 74% and 86% respectively. Conclusions: Compared to the adult literature, TA in children has lower sensitivity, specificity and positive predictive value, but similar negative predictive value for diagnosing nephrolithiasis. This may be related to renal location and smaller stone size. The presence of TA should be weighed in the setting of other clinical and radiographic evidence of nephrolithiasis.